Pengaruh Labelisasi Halal, Customer Trust, dan Brand Image Terhadap Keputusan Pembelian Pada Produk Mixue (Studi Kasus Konsumen Mixue di Kota Malang) - Ula, Siti Nur Syarifatul; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to determine and analyze the effect of halal labeling, customer trust and brand image partially on purchasing decisions for consumers of mixue products in Malang City. The type of research used is quantitative with the method of distributing questionnaires. The sample in this study amounted to 75 respondents and data processing using the SPSS computer program. This study has met the requirements of validity, reliability and normality. The data analysis used in this study is the classical assumption test, multiple linear regression, hypothesis testing and determination coefficient test. The variables used in this study are the dependent variable of purchasing decisions and the independent variables are halal labeling, customer trust and brand image. The results of this study indicate that halal labeling partially has no significant effect on purchasing decisions, but customer trust and brand image partially have a significant effect on purchasing decisions. Simultaneously halal labeling, customer trust, and brand image have a significant effect on purchasing decisions. Keywords: Purchasing Decisions, Halal Labeling, Customer Trust, Brand Image